The Development Of Powtoon-Based Learning Media On Classification Of Living Things To Increase The Learning Interest Of Class VII Students At SMP Plus Ja-Alhaq Bengkulu City - Yuliana, Nur Haviza; Satria, Irwan; Putra, Erik Perdana (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
The aim of this research is to develop powtoon-based learning media on the classification of living things to increase the learning interest of class VII junior high school students. The type of research used in this research is the ADDIE research method which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. This research was carried out at SMP Plus Ja-alHaq, Bengkulu City, involving 10 students in seventh grade and one science subject teacher. So the first step that researchers take is to analyze problems and analyze needs. The next step, the researchers designed a science learning media product using Powtoon by including material on the classification of living things. In the product development stage, a validation test was carried out on the feasibility of powtoon-based learning media by 3 lecturers at Fatmwati Sukarno Bengkulu State Islamic University consisting of 1 material expert lecturer, 1 media expert lecturer and 1 language expert lecturer. Data from questionnaire analysis by calculating the percentage of achievement in each component, namely 94.6% from material experts, 96% from media experts, and 86% from language experts with the category very suitable for use. Data on the practicality of science learning powtoon based on data from student perception responses and science teacher perceptions that researchers developed obtained a percentage value of 94.33% of student perception responses, 95% of science teacher perceptions which were categorized as very practical. The conclusion of this research is that the use of the developed Powtoon -based science learning media is very feasible, and very practical to use as teaching material in supporting the teaching and learning process on the classification of living things for middle school students for class VII of Ja-alHaq Plus Middle School, Bengkulu City. Keywords: Classification of Living Things; Powtoon Based Media; Interest to learn